Rozbieżności pomiędzy Francją i Stanami Zjednoczonymi w sprawie rozbrojenia w dwudziestoleciu międzywojennym - Brzeziński, Andrzej Maciej (Acta Universitatis Lodziensis. Folia Historica, 1995)
The differences concerning disarmament were the permanent feature of the Franch-American relations in Inter-War Period. It was the consequence of the different geographical and political situation, military policy and strategy of the both Powers. The French diplomacy adhered the thesis about priority of security before disarmament and the principle of the interdependence of land, naval and air armaments. The US diplomacy estimated the disarmament as the mean leading to general security. The American concepi of qualitative disarmament of land forces was oriented mainly against France, which at that time, had the biggest amount of military land équipement. The navy fixed for US the most important strategic value, so American diplomacy was very active in the naval disarmament negotiations. France evaluated negatively the American tactic concerning limitation of navel armaments. The Americans wanted to obtain the naval superiority and treated France as secondary naval Power. Paris was opposed to American thesis that disarmament would allow for financial savings and it would facilitate repayment of debts incurred, among others, by France in the United States during the First World War. Contrary to France, US advocated the principle of equal rigts in armaments, which was demanded by Germany. United States, jointly with Great Britain and Italy, pressed on the French Government to accept this principle. Washington remained under a false impression that this concession would prevent Hitler’s armaments demand.